Associations of individual factors and early childhood education and care (ECEC) centres characteristics with preschoolers’ BMI in Germany - Herr, Raphael; Bock, Freia de; Diehl, Katharina; Wiedemann, Eva; Sterdt, Elena; Blume, Miriam; Hoffmann, Stephanie; Herke, Max; Reuter, Marvin; Iashchenko, Iryna; Schneider, Sven (BMC public health, 2022)
The number of obese children is rising worldwide. Many studies have investigated single determinants of children’s body mass index (BMI), yet studies measuring determinants at different potential levels of influence are sparse. The aim of this study is to investigate the independent role of parental socioeconomic position (SEP), additional family factors at the micro level, as well as early childhood education and care (ECEC) centre characteristics at the meso level regarding BMI. Analyses used the baseline data of the PReschool INtervention Study (PRINS) including up to 1,151 children from 53 ECEC centres. Multi-level models first estimated the associations of parental SEP indicators (parental school education, vocational training, and household income) with the children’s standard deviation scores for BMI (SDS BMI, standardised for age and gender). Second, structural (number of siblings), psychosocial (strained family relationships), and nutrition behavioural (soft-drink consumption, frequency of fast-food restaurant visits) family factors at the micro level were included. Third, characteristics of the ECEC centre at the meso level in terms of average group size, the ratio of overweight children in the group, ECEC centre type (all-day care), and the location of the ECEC centre (rural vs urban) were included. All analyses were stratified by gender and adjusted for age, migration background, and parental employment status. Estimates for boys and girls appeared to differ. In the full model, for boys the parental SEP indicators were not related to SDS BMI. Factors related to SDS BMI in boys were: two or more siblings; B = -.55; p = 0.045 [ref.: no sibling]), the characteristics of the ECEC centre in terms of average group size (20 - 25 children; B = -.54; p = 0.022 [ref.: < 20 children]), and the ratio of overweight children (more overweight children B = -1.39; p < 0.001 [ref.: few overweight children]). For girls the number of siblings (two and more siblings; B = .67; p = 0.027 [ref.: no sibling]) and average group size (> 25 children; B = -.52; p = 0.037 [ref.: < 20 children]) were related to SDS BMI. The BMI of preschool children appears to be associated with determinants at the micro and meso level, however with some gender differences. The identified factors at the micro and meso level appear largely modifiable and can inform about possible interventions to reduce obesity in preschool children.